Partial Breast Reconstruction Using Various Oncoplastic Techniques for Centrally Located Breast Cancer - Park, Hyo Chun; Kim, Hong Yeul; Kim, Min Chul; Lee, Jeong Woo; Chung, Ho Yun; Cho, Byung Chae; Park, Ho Yong; Yang, Jung Dug (Archives of Plastic Surgery, 2014)
Background As the breast cancer incidence has increased, breast-conserving surgery has replaced total mastectomy as the predominant procedure. However, centrally located breast cancers pose significant challenges to successful breast-conserving surgeries. Therefore, we performed partial mastectomy and oncoplastic procedures on centrally located breast cancer as a means of partial breast reconstruction. The authors examined and evaluated the functional and aesthetic usefulness of this reconstruction method.Methods From January 2007 to June 2011, 35 patients with centrally located breast cancers who underwent various oncoplastic procedures based on the breast size and resection volume. The oncoplastic procedures performed included volume displacement surgical techniques such as purse-string suture, linear suture, and reduction mammaplasty. Other oncoplastic procedures included volume replacement procedures with an adipofascial, thoracoepigastric, intercostal artery perforator, thoracodorsal artery perforator, or latissimus dorsi flap.Results Mean patient age was 49 years, and mean follow-up period was 11 months. In cases of small to moderate-sized breasts and resection volumes <50 g, volume displacement procedures were performed. In cases of resection volumes >50 g, volume replacement procedures were performed. In cases of larger breasts and smaller resection volumes, glandular reshaping was performed. Finally, in cases of larger breasts and larger resection volumes, reduction mammaplasty was performed. This reconstruction method also elicits a high patient satisfaction rate with no significant complications.Conclusions In centrally located breast cancer, oncoplastic surgery considering breast size and resection volume is safe and provides appropriate aesthetic outcomes. Therefore, our method is advisable for breast cancer patients who elect to conserve their breasts and retain a natural breast shape.
Keywords: Breast neoplasms; Surgical flaps; Mammaplasty